2022
DOI: 10.1111/liv.15461
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate pesticide exposure and biomarkers of liver injury/liver function

Abstract: Background and Aims There is little epidemiological evidence linking the exposure of organophosphate pesticides (OPs) to liver function or liver injury in the general population. We used data from the National Health and Nutrition Examination Survey 1999–2012 to investigate the relationship of urinary OPs with biomarkers of liver function/liver injury. Methods The exposures were the concentrations of urinary OP metabolites (dimethyl phosphate [DMP], dimethyl thiophosphate [DMTP], diethyl phosphate [DEP] and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Environmental pollutants and pesticides have been involved in causing (and worsening pre‐existing) non‐alcoholic fatty liver disease, the so‐called “toxicant” associated steatohepatitis (TASH) being the typical phenotype of liver injury, as, for instance, has been described in workers of the petrochemical industry majority of whom did not have insulin resistance suggesting that fatty liver was a direct effect of the volatile compounds for which they were exposed to 10 . Although Li and coworkers in a recently published article of similar design found that among a mixture of chemical compounds, organophosphate pesticides were associated with fatty liver measured by the liver steatosis indexes, HSI and USFLI (OR: 1.32, 95% CI 1.15–1.51) 11 , in the present study, however, they did not replicate their previous findings 3 . Instead, a novel and intriguing finding of this study is the association of some urinary OP metabolites with parameters of liver fibrosis and liver dysfunction, which suggest that long‐term exposure to these pesticides might apparently lead to subclinical liver damage severe enough to affect liver function.…”
Section: Figurecontrasting
confidence: 99%
See 4 more Smart Citations
“…Environmental pollutants and pesticides have been involved in causing (and worsening pre‐existing) non‐alcoholic fatty liver disease, the so‐called “toxicant” associated steatohepatitis (TASH) being the typical phenotype of liver injury, as, for instance, has been described in workers of the petrochemical industry majority of whom did not have insulin resistance suggesting that fatty liver was a direct effect of the volatile compounds for which they were exposed to 10 . Although Li and coworkers in a recently published article of similar design found that among a mixture of chemical compounds, organophosphate pesticides were associated with fatty liver measured by the liver steatosis indexes, HSI and USFLI (OR: 1.32, 95% CI 1.15–1.51) 11 , in the present study, however, they did not replicate their previous findings 3 . Instead, a novel and intriguing finding of this study is the association of some urinary OP metabolites with parameters of liver fibrosis and liver dysfunction, which suggest that long‐term exposure to these pesticides might apparently lead to subclinical liver damage severe enough to affect liver function.…”
Section: Figurecontrasting
confidence: 99%
“…10 Although Li and coworkers in a recently published article of similar design found that among a mixture of chemical compounds, organophosphate pesticides were associated with fatty liver measured by the liver steatosis indexes, HSI and USFLI (OR: 1.32, 95% CI 1.15-1.51) 11 , in the present study, however, they did not replicate their previous findings. 3 Instead, a novel and intriguing finding of this study is the association of some urinary OP metabolites with parameters of liver fibrosis and liver dysfunction, which suggest that long-term exposure to these pesticides might apparently lead to subclinical liver damage severe enough to affect liver function. The mechanisms for which OP exposure would result in liver fibrosis and hepatic dysfunction are elusive.…”
Section: E D I T O R I a Lmentioning
confidence: 77%
See 3 more Smart Citations